The Effect of Debt Delinquency on Financial Stress Moderated by Financial Capability on Housewives in Regency Housing - Nova Laura Putri Marbun; Ujang Suherman; Rengga Madya Pranata (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the impact of debt delinquency on financial stress, with financial capability considered as a moderating factor among housewives residing in Regency Housing. A quantitative method with an explanatory design was employed, involving a sample of 96 housewives selected through random sampling. Data were obtained via questionnaires and analyzed using multiple linear regression. The findings reveal a positive correlation between debt delinquency and financial stress indicating that greater delays in debt repayment are associated with higher financial stress levels. On the other hand, financial capability appears to reduce financial stress, although the effect is not statistically significant. Furthermore, the study concludes that financial capability does not moderate the relationship between debt delinquency and financial stress. These results underscore the importance of financial education initiatives aimed at helping housewives manage debt more effectively and improve their financial literacy. The study also suggests that enhancing social support systems and ensuring access to formal financial services could help lessen the adverse effects of delayed debt repayments.